(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Breakwater structures are widely used for coastal protection from the blows of ocean waves that propagate to coastal areas. One of the breakwater innovations being developed is the pile structure. Piles are a replication of mangrove tree trunks that can reduce wave energy, so it is necessary to test their effectiveness in reducing wave energy. So the purpose of this study is to analyze the effectiveness of the pile structure by analyzing the wave behavior before and after colliding with the pile structure based on the wave theory division. Physical laboratory simulations have been carried out to obtain wave data that interacts with the pile structure. Furthermore, energy spectrum analysis is used to determine the energy spectrum of the incident wave, reflection and transmission of wave probe measurements in the form of time series data. Each energy spectrum is used to see the reflection and transmission capabilities of the pile structure from the reflection and transmission coefficients. The reflection and transmission coefficient values ​​were estimated using a third degree polynomial equation resulting in RMSE = 0.087 and RMSE = 0.051 with the basic wave parameters being variable, namely wave height, wave period and water depth. The critical point of the polynomial equation shows the minimum reflection and transmission coefficient values ​​when it is in the Cnoidal region and maximum when it is in the 2nd order Stokes region.